ANALISIS PERSEPSI PETERNAK AYAM PEDAGING (BROILER) TENTANG KEMITRAAN DI KECAMATAN PONDOK KUBANG KABUPATEN BENGKULU TENGAH - Yuristia, Rahmi; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
This study aims to analyze farmers' perceptions of partnerships in the Pondok Kubang District. This research was conducted in Bengkulu Tengah Regency, for 5 months from June to October 2019. This type of research is survey research. In this study two types of data are used, namely, primary data obtained from respondents directly and secondary data, obtained from government agencies and related institutions. Measurement of farmers' perceptions and behavior is carried out using a Likert scale or assessment score. Based on the results of the study it was found that farmers 'perceptions of partnerships that have been established are classified as good, this can be seen from the acquisition scores obtained that farmers' perceptions about conformity of opinion with the core company are 75% of farmers answered Fairly Good with an Average Score of 9.75; farmers' perceptions of the socio-economic benefits of the partnership that have taken place are 75% of farmers answering Fairly Good with an Average Score of 10.50, and farmers' perceptions of information disclosure between partner farmers and core companies in the partnership are 100% of breeders answered Good with an average score of 12.25.